Evaluate On the Relationship between Advertising Clutter and Generation Y Negative Attitude toward Television Advertising - Yan, Yuzhen (2013)
Negative attitude towards television (TV) advertising issues also known as ‘advertising avoidance’ are getting serious since recently years which challenges the effectiveness of TV advertising and also the companies choose the advertising channel through TV. Advertising cultures are one of the most important factors which lead the negative attitude towards TV advertising. However, there some advertising companies still unaware about the reason of advertising avoidance especially TV advertising. And the generation Y as new leading group which is the main target group for all kind of industry. However, research on the elements influences generation Y negative attitude towards TV advertising is limited, especially the negative attitude through advertising clutters. Therefore, this study was to adopt advertising clutters factors and generation Y negative attitudes towards TV advertising. It was to evaluate the relationship between advertising clutters and generation Y negative attitude towards TV advertising, which advertising clutters factors have positive influence generation Y built negative attitude towards TV advertising, and which have the strongest influence on generation Y built negative attitude towards TV advertising. And this study has also to look at the difference between demographic factors and generation Y built negative attitude towards TV advertising. To complete this research, a survey method using self – administered questionnaires we carried out to gather data from 385 respondents who are generation Y in university. The result shows the TV advertising excessiveness and annoyance/irritation have positive influence generation Y negative attitude towards TV advertising, and only Indian respondents are have more negative attitude towards than other race in Malaysia. Finally, the last chapter has provided discussion and recommendations.